CONTROLE GENÉTICO PARA CRESCIMENTO VOLUMÉTRICO E MODELOS DE CALIBRAÇÃO NIRS PARA PROPRIEDADES FÍSICAS E QUÍMICAS PARA Corymbia spp. - MIRANDA, LETICIA (2022)
The growth aptitude and wood characteristics of Corymbia species have gained special attention from forest improvement programs in Brazil, however, their potential and genetic variability still need to be explored. Thus, the main objective of this research was to investigate the genetic control of the individual volume trait (VOL), the correlation of this trait at two different ages and the comparison between three different selection intensities (i=1%, i=5% and i= 10%), its effect on genetic gain and effective size of Corymbia populations in Telêmaco Borba, state of Paraná. For this, 10 progeny tests were evaluated, being four tests of C. citriodora (CCT), two tests of C. variegata (CCV) and four tests of C. torelliana (CTO). Narrow-sense heritabilities (ℎ̂𝑎2) ranged from 0,24 to 0,62 between CCT tests, from 0,07 to 0,21 between CCV tests, and from 0,14 to 0,69 between CTO tests. The individual genetic variation coefficients 𝑐𝑣̂𝑔𝑖(%) ranged from 22,5% to 63,9% between the CCT tests, from 20,5% to 32,4% between the CCV tests, and from 22,9% to 41,3% between the CTO tests. Considering a selection intensity (IS) of 10%, the Ne after selection will be between 31 and 98 for the CCT tests, from 36 to 47 for the CCV tests and from 45 to 62 for the CTO tests, and for two CTO tests a selection intensity greater than 10% is recommended. Also considering IS=10%, genetic gains ranged from 37% to 129% for CCT tests, from 30 to 46% between CCV tests, and from 39 to 79% for CTO tests. The genetics correlations 𝑟𝑔(𝑥,𝑦) found for VOL at 2 and VOL at 6 years in a CCT test and VOL at 4 years and VOL at 7 years in two CTO tests, were 0,96; 0,98 and 0,93; respectively. This result points to a high and positive correlation between the ages of 2 and 6 years for CCT and 4 and 7 years for CTO, and the possibility of selection and capture of gains at an early age. The genetic improvement of the populations of the three studied species of Corymbia in the region of Telêmaco Borba, presents significant genetic variability, adequate effective size for the maintenance of the variability, and possibilities of absolute and percentage gains the intensities of selection of 5 and 10%, being able to be early selection an efficient tool for the breeder to use.